2010
DOI: 10.1016/j.ijid.2010.02.1563
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of aminoglycosides resistance in Acinetobacter spp. with emergence of multidrug-resistant strains in hospitalized patients in Iran

Abstract: Background:Acinetobacter spp. is characterized as an important nosocomial pathogen and increasing antimicrobial resistance. Our aim was to evaluate antimicrobial susceptibility and aminoglycosides resistance genes of Acinetobacter spp. isolated from hospitalized patients.Methods:Sixty isolates were identified as Acinetobacter species. The isolates were tested for antibiotic resistance by disc diffusion method for 12 antimicrobials. The presence of aphA6, aacC1 aadA1, and aadB genes were detected using PCR.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
21
4
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 11 publications
9
21
4
1
Order By: Relevance
“…It is necessary to mention that some of these patterns were comparable with other previously reported patterns in different countries or even Iran. For example, resistance to tobramycin and gentamicin in the current study was similar to the rates reported by previous studies in Iran (35,36). The emergence of such MDR and PDR pathogens is a serious crisis in the medical community, an issue that could be solved through development of novel medications.…”
Section: Discussionsupporting
confidence: 89%
“…It is necessary to mention that some of these patterns were comparable with other previously reported patterns in different countries or even Iran. For example, resistance to tobramycin and gentamicin in the current study was similar to the rates reported by previous studies in Iran (35,36). The emergence of such MDR and PDR pathogens is a serious crisis in the medical community, an issue that could be solved through development of novel medications.…”
Section: Discussionsupporting
confidence: 89%
“…More than 60% of Acinetobacter sp. isolates in Iran contained phosphotransferase aphA6 and acetyltransferase genes aacC1,but adenyltransferase genes aadA(41.7%) and aadB(3.3%) were less prominent 21.7% of the strains contain three aminoglycoside resistance genes(aphA6,aacC1 and aadA1) (Moniri et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Many of AME genes are wide spread in Pseudomonas aeruginosa and A. baumanni isolates (Hujer, Hujer, Hulten, Bajaksouzian, & Adams, 2006;Doi & Arakowa, 2007;Dubois, Arpin, Dupart, Scavelli, & Coulange, 2008;Moniri, Farahani, Shajar, NazemShirazi, & Ghasemi, 2010;Aghazadeh et al, 2013) in Escherichia coli and Klebsiella spp. (Haldorsen, Simonsen, & Sundsfiord, 2014) and in Acinetobater spp.,E.coli, Klebsiella spp.…”
Section: Introductionmentioning
confidence: 99%
“…moniri (19) showed 60% resistance against amikacin, ceftazidim, and ciprofloxacin. There is a common significance to all these articles and that is their alarming results about the high resistance of A. baumannii against many used antibiotics.…”
Section: Discussionmentioning
confidence: 99%